The role of diagnostic hysteroscopy in abnormal uterine bleeding and its histopathological correlation following blind dilatation and curettage - Valson, Hariharan; Kulkarni, Chinmay; Mukerjee, Sukanya; Gowda, Shylaja N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is a common gynecological disorder in women. To render appropriate treatment it is vital to establish the correct diagnosis, in this backdrop we have studied the utility of hysteroscopy as a diagnostic procedure against a blind dilatation and curettage. The objectives of the study were hysteroscopic evaluation of abnormal uterine bleeding in reproductive and post-menopausal women. Hysteroscopic findings were compared with the histopathological reports following blind dilatation and curettage. Methods: It is a prospective study on women with symptoms of AUB for a period of one year from Oct 2014 to Nov 2015. Detailed history and clinical examination with an ultrasound (USG) of pelvis to see for endometrial thickness and any structural abnormality was done. 50 cases were included for hysteroscopy. Endometrial biopsy was taken by blind dilation and curettage (D & C) and sent for histopathological examination (HPE). The hysteroscopic and histopathological findings were analyzed. Results: Both hysteroscopy and (D & C) were accurate when an abnormality was diagnosed, giving a specificity of 96.4% and 96.4% respectively and positive predictive value of (95.2% versus 94.4%). The ability to diagnose a lesion was more with hysteroscopy i.e. sensitivity in comparison to curettage, (90.9% versus 77.4%), while a negative diagnosis was less wrongly made with hysteroscopy in comparison to curettage (false negative rate: 9.1% versus 22.7%). In intracavitary lesions like polyp, hysteroscopy gave 100% accuracy. Conclusions: Hysteroscopy is a sensitive diagnostic procedure that provides useful information in all intracavitary lesions and has a higher sensitivity and specificity. A blind D & C for AUB may miss focal lesions including endometrial carcinoma, hence hysteroscopy is advisable.